Quantitative Insights on Impurities in Ice Cores at the Micro‐Scale From Calibrated LA‐ICP‐MS Imaging - Bohleber, Pascal; Larkman, Piers; Stoll, Nicolas; Clases, David; Gonzalez de Vega, Raquel; Šala, Martin; Roman, Marco; Barbante, Carlo (Geochemistry, Geophysics, Geosystems, 2024)
Understanding the microscopic variability of impurities in glacier ice on a quantitative level has importance for assessing the preservation of paleoclimatic signals and enables the study of macroscopic deformational as well as dielectric ice properties. Two-dimensional imaging via laser-ablation-inductively-coupled-plasma-mass-spectrometry (LA-ICP-MS) can provide key insight into the localization of impurities in the ice. So far, these findings are mostly qualitative and gaining quantitative insights remains challenging. Recent advances in LA-ICP-MS high-resolution imaging now allow ice grains and grain boundaries to be resolved individually. These resolutions require new adequate quantification strategies and, consequently, accurate calibration with matrix-matched standards. Here, we present three different quantification methods, which provide a high level of homogeneity at the scale of a few tens of microns and are dedicated to imaging applications of ice cores. One of the proposed methods has a second application, offering laboratory experiments to investigate the displacement of impurities by grain growth, with important future potential to study ice-impurity interactions. Standards were analyzed to enable absolute quantification of impurities in selected ice core samples. Calibrated LA-ICP-MS maps indicate similar spatial distributions of impurities in all samples, while impurity levels vary distinctly: Higher concentrations were detected in glacial periods and Greenland, and lower levels in interglacial periods and samples from central Antarctica. These results are consistent with ranges from complementary meltwater analysis. Further comparison with cm-scale melting techniques calls for a more sophisticated understanding of the ice chemistry across spatial scales, to which calibrated LA-ICP-MS maps now contribute quantitatively.Compared to the large amount of information relating to paleoclimate signals reconstructed from cm-scale impurity measurements on ice cores, knowledge about the spatial ...